Atom‐Mirror Entanglement: Modulation‐Based Atom‐Mirror Entanglement and Mechanical Squeezing in an Unresolved‐Sideband Optomechanical System (Ann. Phys. 7/2019). Issue 7 (9th July 2019) - Bai, Cheng‐Hua; Wang, Dong‐Yang; Zhang, Shou; Liu, Shutian; Wang, Hong‐Fu
Abstract : In article number1800271, Cheng‐Hua Bai, Hong‐Fu Wang, and coworkers investigate the influence of periodic modulation on the macroscopic quantum effects in a hybrid optomechanical system which is composed of an atomic ensemble and a standard optomechanical cavity. They found that, based on the periodic modulation, the atom‐mechanical entanglement can be enhanced, and mechanical squeezing can be successfully induced in the unresolved‐sideband regime.